Co-Simulation of Distributed Engine Control System and Network Model using FMI & SCNSL - Pedersen, Nicolai; Madsen, Jan; Vejlgaard-Laursen, Morten (IFAC-PapersOnLine, 2015)
Increased legislations on engine pollution and efficiency, in the maritime industry, has resulted in drastic changes of engine layout and the amount of interconnected systems. With increased complexity and a more distributed control system, co-simulation and network modelling tools become even more desired. This paper investigates how to co-simulate a distributed cyber-physical system and its surrounding network. The Functional Mock-up Interface (FMI) for co-simulation is used as a standard for interconnecting models and solvers. A network model connecting all subsystem components is created using the SystemC Network Simulation Library (SCNSL). Combining FMI and SCNSL makes it possible to validate the interconnection between both physical and computational components together with the network typology. The result is a more complete simulation environment with better opportunities for investigating proper system behaviour in terms of dynamics and temporal execution. A master algorithm for doing the networked co-simulation routine is proposed, and a proof of concept example is presented, showing one of the many potentials of the environment. With the more comprehensive simulation environment, developers will be able to achieve improved modelling and validation processes, resulting in better applications.